Transcriptome analysis of rice resistant and susceptible near-isogenic lines in response to infection by Xanthomonas oryzae pv. oryzicola - Zhang, Hui; Tang, Min; Wan, Yao; Deng, Ziqiu; Qin, Xuemei; Huang, Jieyi; Wei, Xuan; Li, Rongbai; Liu, Fang (Frontiers in Plant Science, 2025)
Rice bacterial leaf streak (BLS), caused by gram-negative bacterium Xanthomonas oryzae pv. oryzicola (Xoc), is one of the most destructive quarantine diseases internationally. Effectively utilizing BLS resistance genes from wild rice to breed resistant varieties can solve the problem of controlling BLS at its source. In this study, resistant near-isogenic line NIL-bls2 (abbreviated as R) and susceptible near-isogenic line NIL-BLS2 (abbreviated as S) in BC4F3 were constructed by using Guangxi common wild rice material DY19, which carries the BLS resistance gene bls2 and susceptible indica rice variety 9311. Transcriptome sequencing was used to analyze the molecular interaction mechanism of R and S in response to infection by a highly pathogenic Xoc strain gx01. The results showed that between R and S, there were 218 differentially expressed genes (DEGs) at 12 hours post inoculation (hpi), 170 DEGs at 24 hpi, and 329 DEGs at 48 hpi after inoculation. GO and KEGG enrichment analysis revealed that the following changes occurred in R compared to S after Xoc infection: At 12 hpi, R enhanced cell wall toughness by synthesizing lignin; increased the ability to recognize and bind bacterial flagellin flg22, activating multiple immune responses of downstream signal transmission; and promoted wound healing by enhancing the synthesis of traumatic acid. At 24 hpi, R synthesized a large number of diterpenoid phytoalexins, up-regulated genes related to disease resistance protein PR1 and heat shock protein HSP90B, and activated jasmonic acid and salicylic acid-dependent signal transduction pathways. At 48 hpi, R carried out a defense reaction by strengthening the cell wall, enhancing jasmonic acid synthesis, synthesizing monoterpenes and isoquinoline alkaloids, etc. Taken together, bls2 was proposed to regulate both PTI- and ETI-related genes through multi-level defense system, including plant hormone-mediated regulation, antimicrobial phytoalexin biosynthesis, and structural barrier reinforcement, to against Xoc infection. It laid a theoretical foundation for further in-depth research into the molecular mechanism of the BLS resistance gene bls2.